2022
DOI: 10.3389/fnut.2022.926390
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns in Association With Hypertension: A Community-Based Study in Eastern China

Abstract: ObjectiveThis study aimed to explore the association between dietary patterns and hypertension based on a community–based survey in Suzhou, Eastern China.MethodsThis cross–sectional analysis was undertaken from the subset of the Suzhou Food Consumption and Health State Survey in 2018–2019. Adults aged ≥ 18 years were invited to participate in this survey. Dietary intake was collected by a 24–h dietary recall and a weighing method over three consecutive days (including two weekdays and one weekend day). Dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…The southern pattern that was the predominant dietary pattern in China, did not significantly affect BP and the risk of hypertension. This null association observed in our study was consistent with a previous report in a city of Eastern China [ 27 ]. Similarly, a traditional pattern with high loading of cereals and vegetables was not related to the risk of hypertension among Korean women aged 30–79 years [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The southern pattern that was the predominant dietary pattern in China, did not significantly affect BP and the risk of hypertension. This null association observed in our study was consistent with a previous report in a city of Eastern China [ 27 ]. Similarly, a traditional pattern with high loading of cereals and vegetables was not related to the risk of hypertension among Korean women aged 30–79 years [ 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…Similar to our results, a cohort study of middle-aged and elderly men in Shanghai suggested that the ‘fruit and milk’ pattern was significantly associated with both lower SBP and DBP [ 34 ]. Besides, a community–based survey in Eastern China found that the fruit-dairy pattern was inversely associated with the risk of hypertension among the study participants [ 27 ]. The modern pattern in our study had high loadings for fruits, dairy products, eggs and nuts, all of which have been reported to have beneficial effects on BP [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension was defined as blood pressure ≥ 140/90 mmHg, hospital diagnosis, or antihypertensive medication use [23,29] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Information on diabetes, hyperlipidaemia, stroke (ischaemic, haemorrhagic and other types) or other chronic diseases (CHD, chronic obstructive pulmonary disease, asthma, bone and joint disease, neck or waist disease, chronic digestive system disease, chronic urinary system disease, and malignant tumours) was obtained by questioning the participants whether they had been diagnosed by a qualified physician at a township or higher hospital. Hypertension was defined as blood pressure ≥ 140/90 mmHg, hospital diagnosis or antihypertensive medication use (23,29) .…”
Section: Covariatesmentioning
confidence: 99%